Strategic Da’wah Communication of Dewan Masjid Indonesia in Strengthening Religious Moderation at the Community Level - Suharto Suharto; Hasriani Hasriani; Ardillah Abu; Halimah Abdul Manaf (Nyimak: Journal of Communication, 2026)
Religious moderation in Indonesia faces a paradox, on the one hand, it is intensively promoted through state policies and public discourse; on the other hand, practices of intolerance and ideological polarization continue to emerge at the community level. The dominance of normative, top-down approaches in the literature tends to position moderation as a regulatory agenda, while religious social spaces such as mosques where everyday meanings and religious authority are actively produced remain relatively underexplored. Consequently, a theoretical gap persists in understanding how religious moderation is constructed organically through communitarian communication practices. This study examines the communication strategies of the Gerakan Subuh Berkah (GSB), initiated by the Dewan Masjid Indonesia of Palu City, as a mosque-based intervention model for strengthening religious moderation. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis. The findings indicate that GSB has developed a dialogical and inclusive da‘wah ecosystem that integrates congregational worship, persuasive religious education, and participatory social activities. This strategy reinforces social capital (bonding, bridging, and linking), contributing to enhanced social cohesion and the mitigation of radicalization risks. The study underscores that religious moderation is not only effectively advanced through policy instruments but also through sustainable and participatory community-based religious communication.Keywords: Dakwah communication, religious moderation, Gerakan Subuh Berkah, social capital, community resilience ABSTRAKModerasi beragama di Indonesia menghadapi paradox, di satu sisi dipromosikan secara intensif melalui kebijakan negara dan wacana publik, namun di sisi lain praktik intoleransi dan polarisasi ideologis tetap muncul pada level komunitas. Dominasi pendekatan normatif-top down dalam literatur cenderung memposisikan moderasi sebagai agenda regulatif, sementara ruang-ruang sosial keagamaan seperti masjid yang justru menjadi arena produksi makna dan otoritas keagamaan sehari-hari relatif kurang dikaji secara mendalam. Akibatnya, terdapat kesenjangan teoretis dalam memahami bagaimana moderasi beragama dibangun secara organik melalui praktik komunikasi komunitarian. Penelitian ini mengkaji strategi komunikasi Gerakan Subuh Berkah (GSB) yang digagas oleh Dewan Masjid Indonesia Kota Palu sebagai model intervensi berbasis masjid dalam penguatan moderasi beragama. Dengan desain studi kasus kualitatif, data diperoleh melalui wawancara mendalam, observasi partisipan, dan analisis dokumen. Hasil penelitian menunjukkan bahwa GSB membangun ekosistem dakwah dialogis dan inklusif yang mengintegrasikan ibadah berjemaah, edukasi persuasif, dan aktivitas sosial partisipatif. Strategi ini memperkuat modal sosial (bonding, bridging, linking) yang berdampak pada peningkatan kohesi sosial dan mitigasi risiko radikalisasi. Studi ini menegaskan bahwa moderasi beragama tidak hanya efektif melalui instrumen kebijakan, tetapi juga melalui komunikasi dakwah berbasis komunitas yang berkelanjutan dan partisipatif.Kata Kunci: Komunikasi dakwah, moderasi beragama, Gerakan Subuh Berkah, modal sosial, ketahanan masyarakat